2005
DOI: 10.4049/jimmunol.175.1.501
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Phospholipids Negatively Regulate Dendritic Cell Maturation Induced by TLRs and CD40

Abstract: Maturation of dendritic cells (DCs) induced by pathogen-derived signals via TLRs is a crucial step in the initiation of an adaptive immune response and therefore has to be well controlled. In this study, we demonstrate that oxidized phospholipids (ox-PLs), which are generated during infections, apoptosis, and tissue damage, interfere with DC activation, preventing their maturation. ox-PLs blocked TLR-3- and TLR-4-mediated induction of the costimulatory molecules CD40, CD80, CD83, and CD86, the cytokines IL-12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(121 citation statements)
references
References 59 publications
4
116
1
Order By: Relevance
“…4) suggests that OxPAPC does not mediate anti-inflammatory effects via modulation of these mediators. Nevertheless, it should be noted that in certain cell types, such as dendritic cells, OxPAPC may exert immunosuppressive effects independently of its effects on direct inhibition of TLR-signaling pathways (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) suggests that OxPAPC does not mediate anti-inflammatory effects via modulation of these mediators. Nevertheless, it should be noted that in certain cell types, such as dendritic cells, OxPAPC may exert immunosuppressive effects independently of its effects on direct inhibition of TLR-signaling pathways (25).…”
Section: Discussionmentioning
confidence: 99%
“…Because stimulation of Toll-like receptor (TLR) signaling has been shown to play a central role in the induction of inflammation, oxidant release, and tissue damage in many different disease models (21)(22)(23), it is notable that OxPAPC potently inhibits the ability of LPS to stimulate TLR4-dependent signaling in macrophages, dendritic cells, and endothelial cells (3,10,11,17,24,25). The mechanisms by which OxPAPC inhibits LPS signaling are currently under debate, and numerous potential models have been put forward.…”
mentioning
confidence: 99%
“…While the majority of studies attributed a proinflammatory role to Ox-PLs, reports have shown that Ox-PLs can protect mice from endotoxin-induced septic shock [28], down-regulate T cell effector function [29] and inhibit TLR-2-and TLR-4-mediated signalling events in dendritic cells (DC) [30,31], alluding to an anti-inflammatory role for Ox-PLs.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the junctional proteins plakoglobin and N-cadherin, as observed in the MF-lines, has been ELISA; number in parentheses gives concentration of cytokine in pg ml À1 medium. e FACS analyses according to (Pfistershammer et al, 2004;Bluml et al, 2005). Immunoflourescence.…”
Section: Semi-adherent Cells (Blc-lines)mentioning
confidence: 99%
“…Immunoreactions were visualised by application of cye-dye-conjugated secondary antibodies and TCS-SP confocal microscopy (Leica, Heidelberg, FRG). Detailed discription of FACS analyses of the semi-adherent cell lines and antisera applied are given elsewhere (Pfistershammer et al, 2004;Bluml et al, 2005). ELISA-kits were applied according to the manufacturers' instructions.…”
Section: Immunodetectionmentioning
confidence: 99%